2021
DOI: 10.1155/2021/3094571
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Role of Mango Peels in Management of Dyslipidemia and Oxidative Stress in Obese Females

Abstract: Obesity is a chronic metabolic and noncommunicable disease that affects 50% of world population. Reactive oxygen species and oxidative stress are interconnected with the obesity and several metabolic disorders, gaining the attention of scientific community to combat this problem naturally. Among various fruits, mango as a yellow fruit is rich in polyphenols, carotenoids, terpenes, and flavonoids that act as antioxidants to protect against free radicals produced in the body. The present study was performed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…According to Arshad et al [37], the use of mango peel powder can improve lipid profiles in obese women. They also found important antioxidant activity, suggesting that mango peels have a considerable potential to control oxidative stress and dyslipidemia in obese individuals.…”
Section: Indica and Health Effects: Results From Clinical Trialsmentioning
confidence: 99%
“…According to Arshad et al [37], the use of mango peel powder can improve lipid profiles in obese women. They also found important antioxidant activity, suggesting that mango peels have a considerable potential to control oxidative stress and dyslipidemia in obese individuals.…”
Section: Indica and Health Effects: Results From Clinical Trialsmentioning
confidence: 99%
“…Studies in high-cholesterol-fed rats found that consumption of lupeol and its derivatives can reduce the TC triglyceride, and decrease the activity of cardiac enzymes like LDH, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP), thereby suggesting the cardioprotective effects of triterpenoids ( Sudhahar et al, 2007 ). Mango peel powder has shown significant cardioprotective effects in obese females by protecting against vascular damage caused by LDL oxidation ( Arshad et al, 2021 ). Both mango peel extract and mangiferin have been found to produce significant reductions in TG, LDL, and VLDL-cholesterol in the alloxan-induced type I diabetic rat ( Table 1 ; Mistry et al, 2023 ).…”
Section: Management Of Cardiovascular Diseases and Blood Lipid Profilementioning
confidence: 99%
“…Hence, for human behavior changes, joint activities between Universities, Research Centers, Health Ministries, and others will be legally necessary constitution of Departments that could be responsible by outline joint projects and approaches for health promotion through seminars, and lectures to implement in schools (Primary and Secondary), enterprises and families to promote healthy food cooking, sale, and intake to pave the way to reduce obesity and its RMDs prevalence (140)(141)(142)(143)(144).…”
Section: Consumer Behavior Changes On Obesity and Its Rmdsmentioning
confidence: 99%